2020
DOI: 10.1164/rccm.202001-0132ed
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pneumonia in Chronic Obstructive Pulmonary Disease. Have We Unraveled the Network of Risks?

Abstract: Have We Unraveled the Network of Risks? Inhaled corticosteroids (ICS) reduce exacerbation rates in patients with chronic obstructive pulmonary disease (COPD) but may also cause adverse effects, including pneumonia (1, 2). Blood eosinophil counts can predict the clinical response to ICS and ,100 eosinophils/ml is associated with a low probability of a reduction in exacerbation rates (3). Based in part on these data, the use of ICS in clinical practice is becoming more personalized, weighing the possibility of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Lower airway eosinophil numbers are associated with increased presence of colonizing bacteria in stable COPD patients, and ICS use was associated with an increase in bacterial load only in patients with lower eosinophils 6‐9 . Overall, these previous findings suggest that COPD patients with lower eosinophil counts have a different susceptibility to bacterial infection 22 . Our data showing lower immunoglobulin levels and activity in COPD eosinophil low patients provide a potential mechanistic explanation for these observations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Lower airway eosinophil numbers are associated with increased presence of colonizing bacteria in stable COPD patients, and ICS use was associated with an increase in bacterial load only in patients with lower eosinophils 6‐9 . Overall, these previous findings suggest that COPD patients with lower eosinophil counts have a different susceptibility to bacterial infection 22 . Our data showing lower immunoglobulin levels and activity in COPD eosinophil low patients provide a potential mechanistic explanation for these observations.…”
Section: Discussionsupporting
confidence: 63%
“…[6][7][8][9] Overall, these previous findings suggest that COPD patients with lower eosinophil counts have a different susceptibility to bacterial infection. 22 Our data showing lower immunoglobulin levels and activity in COPD eosinophil low patients provide a potential mechanistic explanation for these observations. The risk of pneumonia in COPD patients is associated with certain clinical characteristics, such as previous pneumonia events, age and lower body mass index.…”
Section: Discussionmentioning
confidence: 58%
“…50 Overall, these findings implicate interactions between eosinophilic inflammation and the microbiome that influence ICS response. 51,52 Multiple studies have demonstrated statistically significant associations between blood and lung eosinophil counts, but the strength of the relationship has been weak to moderate. 8 Technical issues such as the quality of sputum slides can negatively impact this relationship.…”
Section: Blood Eosinophils: a Biomarker To Guide Ics Usementioning
confidence: 99%
“…Sometimes blood eosinophils also have been shown to have a protective effect in COPD. Higher blood eosinophils have been associated with fewer infections and possibly a better survival, but the mechanisms to explain these findings have not been defined [ 40 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: The Eosinophilic Copd Phenotype and Future Riskmentioning
confidence: 99%